Pearson Correlation Analysis Between Carbon Dioxide Emissions and Socioeconomic Factors Across Nations' Income Groups - Yuting Qin; Min Yee Chin; Zheng Xuan Hoy; Chew Tin Lee; Musharib Khan; Kok Sin Woon (Chemical Engineering Transactions, 2023)
Excessive carbon dioxide (CO2) emissions are driving unprecedented climate changes, necessitating a comprehensive understanding of the underlying socioeconomic factors to develop effective policies for limiting global CO2 concentrations. Current research lacks a broad global perspective that classifies countries based on income levels, limiting our ability to identify specific challenges and opportunities within different economies. This study aims to fill this gap by investigating the correlation between CO2 emissions and socioeconomic factors in ten (10) high-income and lower-middle-income countries. Through Pearson correlation analysis, the study examines the relationship between CO2 emissions and key indicators such as gross domestic product, population, energy consumption, renewable energy usage, and energy intensity from 1991 to 2021. Among the ten countries studied, the socioeconomic factors of high-income countries are more negatively correlated to carbon emissions, while lower-middle-income countries are more positively correlated. Both income groups have a positive correlation between energy consumption and carbon emissions. This research contributes to evidence-based policymaking and promotes sustainable development practices, offering valuable guidance for policymakers worldwide to combat climate change and reduce carbon emissions across diverse income groups.